PENGARUH KADAR PROTEIN PAKAN TERHADAP PENAMPILAN PERTUMBUHAN, KEMATANGAN GONAD DAN FEKUNDITAS IKAN KATUNG (Pristolepis grooti Bleeker) MATANG GONAD PERTAMA - Hamdan Alawi; Netty Aryani; Nur Asiah (Jurnal Akuakultur Rawa Indonesia, 2015)
ABSTRACT The effect of three protein levels of commercial diet on the growth performance, gonad maturation and fecundity of first maturity of Indonesian leaffish (Pritolepis grooti) was conducted in 54 liters recirculation aquaria system for 10 months rearing period. Eight-week-old artificial spawned  Indonesian  leaffish katung (Pristolepis grooti Bleeker)) fry with an average weight (SD) of 0.560(0.116) g were fed  5% BW three times a day with commercial diets 18, 28 and 38% Protein.  Fish fed on 38%  protein diet showed better growth and feed conversion ratio than those fed on 28 and 18% diets. Males matured earlier than females: the firstmature males were recorded when they were 5 months old, whereas the females matured after 6 month rearing period. The mean percentage of mature female fish rose with increasing feed protein level. It was also found that the percentage of mature fish rose with the increasing fish age and size. More than 70% males matured at the age of 6 months in all diet. After 10 months rearing period, the percentage of matured female fed on 38% protein was 100% while those fed on 16% protein was 25%. Smallest size at spawning of males and females was 8.5 cm (23 g) and 13 cm (65 g), respectively, and dietary protein levels influenced the size of fish at first maturity. It was found that  the protein level significantly effected the gonado somatic index (GSI). Fecundity increased with increasing dietary protein level. The relative fecundity (eggs /g or cm female) was higher at the higher  dietary protein level.   Keywords : Dietary Protein; Growth; Gonad Maturation; Fecundity; Indonesian leaffish Pristolepis grooti